A numerical technique to solve a problem of the fluid motion in a straight plane rigid duct with two axisymmetric rectangular constrictions - Borysyuk, A.O. (Доповіді НАН України, 2022)
A second-order numerical technique is developed to study the steady laminar fluid motion in a straight two-dimensional
hard-walled duct with two axisymmetric rectangular constrictions. In this technique, the governing relations
are solved via deriving their integral analogs, performing a discretization of these analogs, simplifying the obtained
(after making the discretization) coupled nonlinear algebraic equations, and the final solution of the resulting
(after making the simplification) uncoupled linear ones. The discretization consists of the spatial and temporal parts.
The first of them is performed with the use of the TVD-scheme and a two-point scheme of discretization of the
spatial derivatives, whereas the second one is made on the basis of the implicit three-point asymmetric backward
differencing scheme. The above-noted uncoupled linear algebraic equations are solved by an appropriate iterative
method, which uses the deferred correction implementation technique and the technique of conjugate gradients,
as well as the solvers ICCG and Bi-CGSTAB. Розроблено чисельний метод розв’язування задачі про стаціонарний ламінарний рух рідини у прямому
плоскому жорсткому каналі з двома осесиметричними прямокутними звуженнями. Цей метод має другий
порядок точності. У ньому співвідношення, що описують зазначений рух, розв’язуються шляхом одержання їхніх інтегральних аналогів, дискретизації цих аналогів, зведення зв’язаних нелінійних алгебраїчних
рівнянь (одержаних внаслідок дискретизації) до відповідних незалежних лінійних і подальшого
розв’язування останніх. Зазначена дискретизація складається із просторової та часової частин. Перша з
них виконується на основі використання TVD-схеми, а також двоточкової схеми дискретизації просторових похідних. При проведенні ж другої частини дискретизації застосовується неявна триточкова несиметрична схема з різницями назад. Що стосується методу розв’язування вказаних незалежних лінійних рівнянь, то це — відповідний ітераційний метод, який використовує методи відкладеної корекції та
спряжених градієнтів, а також солвери ICCG та Bi-CGSTAB.